Diva over Divine: Towards a Historically Informed Performance of the Sacred Solo Motet in Early-Eighteenth Century Venice - Sarginson, Rebecca L. (2021)
In preparation for a performance, a musician may ask “how was it performed?”; “how could it be performed?”; “Can I perform it in a similar way to...?”. For singers wishing to perform the music for solo voice heard in the sacred institutions of early-eighteenth century Italy, the questions are left unanswered. In the broad field of vocal performance practice, the corner in which eighteenth-century sacred vocal music stands remains in shadow. Histories of eighteenth-century music skim the surface of sacred repertoire and leave the genres, and their performance, undisturbed. Those that do illumine the sections of this rich history often stay at the surface and write overviews of a genre in a location. A lack of study has left much repertoire neglected and so modern performers lack the knowledge to access the repertoire and realise it in performances. In a bid to suggest answers to the questions of a performer, I have chosen to investigate the performance of the solo motet in the context of sacred 1720-50s Venice. This thesis explores the position of the solo motet genre in early eighteenth-century Venice, it’s role as a point of intersection between the secular and sacred musical spheres and seeks to answer the question: would the performance of a sacred solo motet employ the same performance practice as that of a secular cantata or operatic aria? Specifically, I explain how the solo motet interacted with Venice’s social, political and musical contexts. I place the solo motet as a vehicle for secular vocal performance practice in the churches of the Venetian ospedali. This acts as context for a case study which focuses on the Motetto a voce sola con instrumenti by Nicola Porpora for Graziosa in 1744. To form an idea of the performance practice employed by the original soloist, I will evaluate the vocal tuition received by the members of the figlie del cori, and the practice this facilitated, and the popular performance practice discussed in the treatises of Pier Francesco Tosi and Giocomo Mancini. I will compare the employment of virtuosic ornamentation in the solo motet to contemporary secular opera arias and cantatas. This thesis will be drawn to conclusion with a historically informed performance edition of the first aria of the solo motet.